Chapitre 2. Le mouvement anti-esclavagiste et la naissance des droits des femmes. - Davis, Angela Yvonne (Femmes, race et classe, 1983)
Etude socio-historique de la condition des femmes noires aux Etats-Unis; aspect particulier de l'esclavage des femmes noires; persistance des problèmes après l'abolition de l'esclavage.
Section: 341 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; corps; cours; discipline; droits des femmes*; esclavagisme; féminisme afroaméricain; féminismes noirs; histoire et politique; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; états-unis

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Le texte suivant : Owens, Craig. (1983). The Discourse of Others: Feminists and Postmodernism, 57-82 a été donné en lecture au cours HAR4600.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Section: xvi, 175 pages ; 22 cm
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

La lutte pour le droit à l’avortement (1969-1981) - Lamoureux, Diane (Revue d'histoire de l'Amérique française, 1983)
Number: 1 https://id.erudit.org/iderudit/304126ar
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amérique du nord; amériques; avortement; canada; discipline; front de libération des femmes; histoire; justice reproductive; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques

Nous sommes le produit d’un contexte - O'Leary, Véronique; St-Pierre, Josée.; Toupin, Louise (Québécoises deboutte! Tome 1. Une Anthologie de textes du Front de libération des femmes (1969-1971) et du Centre des femmes (1972-1975)., 1983)
Le volume 1 (212 p.) comprend des tracts, documents internes, manifestes et lettres diffusées par les deux groupes entre 1969 et 1975, de même qu'un aperçu de la couverture de presse dont ils bénéficièrent à l'époque. Le volume 2 (377 p.) reprend la collection complète du journal ##Québécoises deboutte## publié entre 1972 et 1975, par le Centre des femmes; on y a ajouté des tables rondes.
Section: 2 volumes : illustrations ; 28 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; histoire et politique; inégalités; militance; postmodernisme; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques

La Québécoite: roman - Robin, Régine (Québec-Amérique, 1983)
Sous le regard de l'Autre. Par l'auteure d'Histoire et linguistique (Colin, 1973) et d'une étude sur l'écriture juive (Le Sorbier, 1983), un récit dans lequel ce professeur d'université française, d'origine judéo-russe, qui enseigna à Montréal, Laval et Sherbrooke relate, pour le bénéfice de ses étudiants, l'histoire de sa découverte du Québec entre 1974 et 1981. Régine Robin, de formation marxiste, manifeste une attention particulière aux luttes ouvrières (grèves, etc.), politiques, idéologiques. L'éditeur parle avec justesse d'un livre d'émigrante sur l'exil, la langue et la vie d'ici. Composition en mosaïque. Inventaires, comparaisons, fragments, altérités.
Section: 200 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; cours; discipline; disicpline; histoire et politique; immigration; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"–
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis